Caring Of Health Officers in Administrative Services, Satisfaction of Inpatient Room Patients at the Muna Regency General Hospital - Rasniah Sarumi; Elna Sari; Nur Yazlim (Politeknik Karya Persada Muna, 2021)
Baground: One form of service in the administration room is the caring behavior of health workers where the caring attitude will be intertwined with a relationship of mutual trust, compassion and honesty. Patients and their families will feel satisfied if the health services received are in accordance with the patient's expectations and can feel disappointed if the caring health workers received are not in line with their expectations so that patients will tend to choose health services that can provide good caring. The purpose of this study was to know the caring of health workers in administrative services on patient satisfaction in inpatients at the Muna Regency General Hospital.. Method: The research design uses a cross sectional study approach involving a sample of 52 people. The data collection method used primary data and secondary data. Data analysis using Univariate and Bivariate analysis. Results: there is a relationship between caring for health workers in administrative services to patient satisfaction in inpatients at the Muna Regency General Hospital with a value of 0,017. Conclusions: there is a relationship between caring for health workers in administrative services to patient satisfaction in inpatients at the Muna Regency General Hospital. Keywords: career, health workers, administrative services, patient satisfaction Pendahuluan: Salah satu bentuk pelayanan diruangan administrasi adalah perilaku caring petugas kesehatan dimana sikap caring akan terjalin dengan adanya hubungan saling percaya, belas kasih dan kejujuran. Pasien maupun keluarga pasien akan merasa puas apabila pelayanan kesehatan yang diterima sesuai dengan harapan pasien dan dapat merasa kecewa bila caring petugas kesehatan yang diterima tidak sesuai dengan harapannya sehingga pasien akan cenderung memilih pelayanan kesehatan yang dapat memberikan caring dengan baik. Tujuan penelitian ini adalah diketahinya caring petugas kesehatan pada pelayanan administrasi terhadap kepuasan pasien di rawat inap Rumah Sakit Umum Daerah Kabupaten Muna. Metode: Desain Penelitian menggunakan pendekatan Cross Sectional Study yang melibatkan sampel sebesar 52 orang. Metode pengumpulan data menggunakan data primer dan data sekunder. Analisis data menggunakan analisis Univariat dan Bivariat. Hasil: ada hubungan caring petugas kesehatan pada pelayanan administrasi terhadap kepuasan pasien di rawat inap Rumah Sakit Umum Daerah Kabupaten Muna dengan nilai ρ sebesar 0,017. Kesimpulan: ada hubungan caring petugas kesehatan pada pelayanan administrasi terhadap kepuasan pasien di rawat inap Rumah Sakit Umum Daerah Kabupaten Muna Kata kunci: caring, petugas kesehatan, pelayanan administrasi, kepuasan pasien